References Supporting Recommendations in Obstetrical Green Top Guidelines: An Overview of RCOG Clinical Guidelines - Soylu, Halime Meryem; Mendez-Figueroa, Hector; Chauhan, Suneet P.; Huntley, Benjamin J.F. (American Journal of Perinatology, 2025)
Green-top Guidelines (GTGs) by the Royal College of Obstetrics and Gynecology (RCOG) guide clinical practices similar to Practice Bulletins (PBs) by the American College of Obstetrics and Gynecology (ACOG). Previous analyses reveal that most recommendations lack Grade A evidence and are not based on randomized clinical trials (RCTs). This descriptive study evaluates the quality of evidence supporting RCOG Obstetrical recommendations.We reviewed obstetrical RCOG GTGs available as of September 2024, checking each citation in PubMed for RCT status. Quality assessments were not made independently. The senior author verified a random 10% of the data (B.J.F.H.). Data were recorded and summarized in Excel.RCOG lists 37 obstetrical GTGs with 1,861 recommendations. About 1,288 (69%) of recommendations are supported by 3,674 references. A total of 43% of GTGs rely on consensus and expert opinion. When omitting recommendations based on expert opinion, 98 (9%) of RCOG recommendations are Grade A (based on high-quality evidence), and of the cited references, 5% of GTGs are Evidence Level 1 + + (highest quality), while 7% are RCTs.Among the recommendations, 69% of GTGs have identifiable references. However, 43% of GTG references are nonanalytical studies or expert opinions. Our findings highlight the need for more high-quality evidence in guidelines and suggest further research in evidence-based obstetrical care.
Keywords: Green-top Guidelines; evidence-based medicine; quality of evidence; expert opinion in guidelines